Effect of placental tissue freeze-thawing modes on composition and biological activity of its cryoextracts - Chyzh, Yuliia; Marchenko, Larysa; Govorukha, Tetiana; Repin , Mykola (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):308